2021
DOI: 10.3390/jcm10225445
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Selected Baseline and Post-PCI Electrocardiographic Parameters as Predictors of Left Ventricular Systolic Dysfunction after a First ST-Segment Elevation Myocardial Infarction

Abstract: Objective: To assess the performance of ten electrocardiographic (ECG) parameters regarding the prediction of left ventricular systolic dysfunction (LVSD) after a first ST-segment-elevation myocardial infarction (STEMI). Methods: We analyzed 249 patients (74.7% males) treated with primary percutaneous coronary intervention (PCI) included into a single-center cohort study. We sought associations between baseline and post-PCI ECG parameters and the presence of LVSD (defined as left ventricular ejection fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Higher peak creatine kinase levels and a higher incidence of severe LVSD were also found when complete ST-segment resolution was not achieved. 19,22 As per previous published study, 86 percent of cases had TIMI flow grade III recovery after pPCI, and that low systolic BP, old age and the occurrence of blood clots in the culprit coronary lesions were independent predictive factors for TIMI flow grade III recovery. 23 STR has been shown to be a stronger predictive marker than epicardial blood flow recovery.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Higher peak creatine kinase levels and a higher incidence of severe LVSD were also found when complete ST-segment resolution was not achieved. 19,22 As per previous published study, 86 percent of cases had TIMI flow grade III recovery after pPCI, and that low systolic BP, old age and the occurrence of blood clots in the culprit coronary lesions were independent predictive factors for TIMI flow grade III recovery. 23 STR has been shown to be a stronger predictive marker than epicardial blood flow recovery.…”
Section: Resultsmentioning
confidence: 55%
“…In compared to partial (30-70%) or no (30%) STsegment resolution, complete (70%) resolution predicts lower 1-3year mortality and lower incidence of cardiovascular potential complications, as well as greater maintenance of left ventricular function. 19,20 Even after successful primary PCI, the benefits of early complete resolution of ST-segment elevation can be demonstrated, with early (i.e., immediately after PCI) testing being more accurate in terms of predicting CVD adverse events than evaluation after 90 minutes. 19,21 Furthermore, patients who had early ST-segment resolution had a larger LVEF than those who had ST-segment resolution after 90 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, six groups of SD rats were generated: CON (saline pretreatment for 4 days followed by normal saline injection, n = 5), ISO (saline pretreatment for 4 days followed by isoproterenol injection, n = 5), IX-L (31.25 mg/kg XML pretreatment for 4 days followed by isoproterenol injection, n = 5), IX-M (62.5 mg/kg XML pretreatment for 4 days followed by isoproterenol injection, n = 6), IX-H (125 mg/kg XML pretreatment for 4 days followed by isoproterenol injection, n = 5), and IP (propranolol pretreatment for 4 days followed by isoproterenol injection, n = 5) ( Figure 1A ). Electrocardiograph (ECG) is the most common test used in the clinic to assess suspected or known cases of myocardial ischemia ( Fabiszak et al, 2021 ). Changes in the ST segment and T-wave should be observed if myocardial ischemia has occurred ( Thygesen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study found STR to be an independent and significant predictor of mortality after 6 months ( p < 0.001). In a previous study that aimed to use baseline electrocardiographic parameters as predictors of impaired LV systolic function in patients who underwent PCI due to first-time STEMI, the authors noted that patients with complete (≥ 70%) resolution of ST-segment elevation had lower 1–3-year mortality and lower rates of cardiovascular adverse events, and had better preservation of left ventricular function in comparison with partial (30–70%) or no (< 30%) ST-segment resolution [ 31 ].…”
Section: Discussionmentioning
confidence: 99%